2022
DOI: 10.1021/acssynbio.2c00119
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Analytical Approaches for Improving the Resolution of Randomly Barcoded Transposon Insertion Sequencing (RB-TnSeq) Studies

Abstract: Randomly barcoded transposon insertion sequencing (RB-TnSeq) is an efficient, multiplexed method to determine microbial gene function during growth under a selection condition of interest. This technique applies to growth, tolerance, and persistence studies in a variety of hosts, but the wealth of data generated can complicate the identification of the most critical gene targets. Experimental and analytical methods for improving the resolution of RB-TnSeq are proposed, using Pseudomonas putida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…To extract barcodes by regular expressions, a set of five custom regular expressions of increasing leniency were composed for each dataset to extract barcode sequences based on the read sequences from each dataset. For example, we used these five regular expressions successively to find barcodes in the reads from the Borchert et al ( 2022 ) dataset (stopping if the regular expression found a match):…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To extract barcodes by regular expressions, a set of five custom regular expressions of increasing leniency were composed for each dataset to extract barcode sequences based on the read sequences from each dataset. For example, we used these five regular expressions successively to find barcodes in the reads from the Borchert et al ( 2022 ) dataset (stopping if the regular expression found a match):…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have successfully tracked K = 10 5 to K = 10 6 lineages ( I min between 16.6 and 19.9 bits and correspondingly L min between 8.8 and 10 bp) with barcodes with length between 15 and 20 bp and information content between 30 and 40 bits (see Fig. 1 A; Levy et al 2015 ; Johnson et al 2019 ; Jasinska et al 2020 ; Ge et al 2020 ; Eyler et al 2020 ; Borchert et al 2022 ).…”
Section: Barcode Design Synthesis and Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Reads mapping to different insertion sites within the same coding sequence were pooled for subsequent analyses. Two sample T tests with multiple comparison adjustment (FDR) were used to identify enrichment or depletion of normalized reads for each transporter on a given substrate relative to all other substrates tested, a modification of the reference medium method for RB-TnSeq analysis described in Borchert et al [ 49 ]. To display enrichment or depletion of multiple transporters and substrates on the same scale, we calculated the fold change of each transporter’s normalized abundance for a given substrate relative to the normalized abundance of that transporter on all other substrates.…”
Section: Methodsmentioning
confidence: 99%